The Spartan Army in the reign of Agesilaos II - Makólski-Świercz, Tomasz (Polskie Towarzystwo Filologiczne, 2019)
This paper is a summary of a PhD thesis that was completed as part of the project “The Eastern Mediterranean from the 4th Century BC until Late Antiquity”. The project was coordinated by Professor Krzysztof Nawotka (University of Wrocław, Institute of History) and took place between 2011 and 2015 within the International PhD Projects Programme of the Foundation for Polish Science, co-financed by the European Union from the Regional Development Fund within the framework of Measure 1.2 “Strengthening the Human Potential within the Science Sector” which was part of the Operational Programme “Innovative Economy”. The thesis was supervised by Professor Ryszard Kulesza (University of Warsaw) and defended at the Department of History, University of Wrocław, on 13th December 2017
Keywords: Agesilaos II; Spartan army